Sveriges irredenta : försvenskningen av de finskspråkiga i Norrbotten 1888-1921 ur identitetsbyggandets synvinkel - Varajärvi, Marko (2009)
In this study the task is to point out the key features in the making of a Swedish nation from the perspective of a minority language, i.e. the Finnish speaking minority in the region of Norrbotten, Sweden. Swedish historians usually list the fear of Russia (Russia, the arch-enemy -topos) and the Laestadian movement as main reasons for the policy of cultural assimilation of the Finnish-speaking minority. In this study the main task is to use the post modern discourse analysis (especially Michael Shapiro) in reading texts between the years 1888 and 1921. For this purpose I have gone through material of the period, i.e. debates in the Swedish Parliament, the newspaper Haparandabladet, pamflets and books etc. The key point is to point out the different methods and reforms applied in the making of a Swedish speaking nation. This means that the periphery - the Finnish speaking people in the Norrbotten-region as objects of reforms - is connected to the centre by different policies of building a Swedish-speaking nation. The different reforms (the school reform and especially the state-school reform in 1888, the building of the railways to Norrbotten, the discussions around the compulsory military service and suffrage reforms etc) are enlightened through this minority perspective and through the discourse analysis of the selected texts. This minority perspective, a potential Finnish irredenta in Norrbotten, is also put in the context of geopolitics. Rudolf Kjellén is often titled as the father of geopolitics. In his writings the Finnish-speaking minority is a central element. This minority is displayed as a central question, a true state-interest which cannot be neglected. The building of a Swedish-speaking nation is also connected to an international context. The central conclusion in this study is to show that in the argumentation of the cultural assimilation of the Finnish-speaking minority especially among the conservative Right in Sweden used the argumentation and the arguments were used in an innovative way. The key was not in the correctness of the arguments but in the effects the arguments had. The aim was to make or build a homogenic Swedish-speaking nation in which the Finnish-speaking were assimilated. This was not an isolated phenomenon, historical warning-examples were often used.